University Teams’ Learning from Collaborative Experiences, with Communities and Social Organizations Supported by the Argentine University Voluntary Work Program, in 2008 - Mato, Daniel (2013)
This article discusses some learning achieved by university teams through their extra-curricular activities carried out in collaboration with communities and social organizations. The research studies fifty-eight diverse experiences, developed by teams constituted by professors and students from different disciplines, some of them interdisciplinary, from twenty Argentine public universities, in varied social contexts. Some of these experiences are conceptualized by their participants in terms of university extension, social reach, service learning, action-research, or university voluntary work. Their common characteristic is that all of them have received support from the University Voluntary Program of the Secretary of University Policies, of the Ministry of Education of Argentina, in 2008.